Pengaruh Model Discovery Learning terhadap Hasil Belajar Peserta Didik pada Pembelajaran IPAS di SD - Syafira, Lara; Aprilianti, Raidha Elsa; Adrias, Adrias; Alwi, Nur Azmi (Lembaga Yasin AlSys, 2024)
This research aims to see the influence of the Discovery Learning model on science learning outcomes in Class V of SD Negeri 03 Bandar Buat. The type of research in this research is Quasi Experimental using a pretest-posttest control group design. This research instrument is an objective test in the form of multiple choices. For initial data, analysis was used using the normality test, homogeneity test and hypothesis test. Based on the results of data analysis, the average value of the pretest results for the experimental class was 68.63 and the control class was 65.33. After being given treatment in the experimental class using the Discovery Learning model and the control class using the conventional approach, the average posttest result for the experimental class was 86.37 and the control class was 76.96. The results of data analysis from the hypothesis tests that have been carried out, obtained tcount 5.010 and ttable 2.006. This means that tcount > ttable, namely 5.010 > 2.006, then the hypothesis Ha is accepted and H0 is rejected, namely that there is an influence of the Discovery Learning model on science and science learning in Class V SDN 03 Bandar Buat, Padang.